Triggers for arrhythmogenesis in the Brugada and long QT 3 syndromes. Issue 1 (January 2016) - Peters, Colin H.; Abdelsayed, Mena; Ruben, Peter C.
Abstract: Cardiac arrhythmias are a prevalent cause of morbidity and mortality. In many cases, inheritable mutations in the genes encoding cardiac ion channels are the underlying cause of arrhythmias. Relative to other arrhythmogenic disorders, Brugada syndrome (BrS) is recently identified and not well-understood. Although most often referred to as a disease of cardiac sodium channels, familial BrS is now associated with 9 different genes. Of these genes, 4 alter sodium currents, and the most common known genetic cause remains loss-of-function mutants in the cardiac sodium channel gene SCN5A. Long QT syndrome (LQTs) has a much longer history and is associated with at least 17 genes. LQT3, which is the third most common LQTs, is due to gain-of-function mutations in SCN5A. The first sign for BrS and LQTs patients may be sudden death. The triggers for these sudden deaths include exercise, fever, ischemia, and drug use. In this paper we review the effects of acidosis and fever on BrS and LQTs, discuss Brugada phenocopy syndrome drawing from published literature, and present our own patch-clamp data from mutant channels at low pH. We show that, at low pH, there is a preferential block of peak currents and preferential increase of persistent current in a common BrS/LQTs mutant compared to wild type sodium channels. Our data complements the existing literature on the importance of environmental triggers to arrhythmias.